Butyronitrile latex gloves with high filling amount of nano calcium carbonate and monodisperse nano calcium carbonate slurry with ultralow calcium ion activity adopted by butyronitrile latex gloves
By using ultra-low calcium ion activity monodispersed nano calcium carbonate slurry as filler in the production of nitrile latex gloves, the problem of low addition of inorganic filler is solved, the mechanical properties and production stability of the gloves are improved, and the cost is reduced.
Patent Information
- Application Number
- CN202411920919.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The amount of inorganic filler added in the existing nitrile latex gloves is not high, resulting in poor reinforcement effects, local defects and poor production process stability of latex products.
The ultra-low calcium ion activity monodispersed nano calcium carbonate slurry is used as a filler. By adding nano calcium carbonate to the nitrile latex high filling amount, it ensures that it has excellent aqueous dispersion and ultra-low calcium ion activity in nitrile latex gloves.
The tensile strength and elongation of nitrile latex gloves are improved, the formulation cost is reduced, and the stability of the production process is ensured. Compared with latex gloves with the same mass of water-ground light calcium, the tensile strength is increased by 30%, the elongation rate of break is increased by 20%, and the formula cost is reduced by 20%.
Smart Images

Figure BDA0005207965550000131 
Figure BDA0005207965550000141 
Figure HDA0005207965560000011
Abstract
Description
Technical Field
[0001] The invention relates to the field of nitrile latex gloves production, and in particular to nitrile latex gloves with a high filling amount of nano-calcium carbonate and monodisperse nano-calcium carbonate slurry with ultra-low calcium ion activity. Background Art
[0002] Nitrile latex gloves are made of nitrile latex as the main raw material, with vulcanizing aids, defoaming agents and other materials, and are prepared through a dipping molding process. Its main raw material, nitrile latex, is made from acrylonitrile and butadiene through emulsion polymerization. The nitrile latex gloves made of it will not cause skin allergies, and the wearing comfort of the products is close to that of natural latex gloves. They are widely used in the fields of medicine, beauty, semiconductors, precision electronic components, etc. With the further expansion of the application market of nitrile latex gloves in recent years, its quality and production costs have been challenged even more.
[0003] A small amount of water-ground light calcium may be added to the production formula of traditional nitrile latex gloves, and even no inorganic filler may be added. The main reasons are as follows: 1) The addition of inorganic fillers will cause the flexibility and ductility of nitrile latex gloves to decrease, resulting in reduced wearing comfort; 2) The addition of water-ground light calcium, which is commonly used in latex production, will cause the mechanical properties of the gloves to decrease due to excessive particle size and poor dispersibility; 3) Nano calcium carbonate, which is commonly used in coatings and other fields, has high surface energy and is easy to agglomerate, which will significantly damage the strength of latex products, so it is difficult to use in latex products; 4) Traditional nano calcium carbonate has defects in development, and the calcium ion concentration in its dispersion is high, which reduces the stability of latex during the production and processing of latex products, affecting normal production. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a nitrile latex glove with a high filling amount of nano-calcium carbonate and a monodisperse nano-calcium carbonate slurry with ultra-low calcium ion activity used therein in view of the deficiencies in the above-mentioned prior art, so as to solve the problems in the prior art of low addition amount of inorganic filler, poor reinforcement effect of latex products, local defects and poor stability of production process, etc.
[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0006] A nitrile latex glove with a high filling amount of nano-calcium carbonate. The raw materials thereof include, by mass, 100 parts of nitrile latex, 0.5-4.8 parts of casein, 2.3-3.4 parts of a mixing aid, 0.6-1.2 parts of cellulose, 5-25 parts of ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry and 0.1-1.5 parts of a defoaming agent; wherein the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry is an aqueous slurry with monodisperse nano-calcium carbonate as a main effective component.
[0007] Preferably, the mass fraction of the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry is 10 to 15 parts.
[0008] In the present invention, the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry comprises, by weight, 100 parts of monodisperse nano-calcium carbonate filter cake, 0.2-2 parts of calcium carbonate surface capping agent, 0.5-1 part of calcium ion complexing agent, 5-10 parts of potassium hydroxide solution and 180-200 parts of water; wherein the concentration of the potassium hydroxide solution is 5-15wt%.
[0009] Furthermore, the water content of the monodisperse nano calcium carbonate filter cake is not more than 40%, the calcium carbonate particle size is small, the average particle size is 50-100nm, the particles larger than 200nm account for less than 5%, and it is in a monodisperse state, with a specific surface area of 19-25m 2 / g, and the content of harmful metal elements is less than 200ppm. The calcium carbonate particles in the monodisperse nano calcium carbonate filter cake have low surface energy and good dispersibility when added to nitrile latex; at the same time, the calcium ion activity in the ultra-low calcium ion activity monodisperse nano calcium carbonate slurry is low, and there is no flocculation risk when added to nitrile latex.
[0010] Furthermore, the calcium carbonate surface capping agent includes one or more of sodium hexametaphosphate, sodium polyacrylate, sodium methylene bisnaphthalene sulfonate, etc.; the calcium ion complexing agent includes one or more of sodium citrate, aminotri(methylenephosphonic acid), disodium ethylenediaminetetraacetate, 4A molecular sieve, 4A zeolite, montmorillonite, etc.
[0011] In the present invention, the nitrile latex is high nitrile, wherein the mass percentage of acrylonitrile is about 35% to 50%; the casein is commercially available edible casein; the cellulose is hydroxymethyl cellulose; and the defoamer is an organosilicon defoamer.
[0012] In the present invention, the mixing aid is an aqueous solution including a vulcanizing agent, a vulcanization activator, an accelerator, a dispersant, and an antioxidant. Specifically, the mixing aid comprises the following components by mass: 100 parts of solvent water, 20 to 40 parts of sulfur, 15 to 25 parts of zinc oxide, 5 to 15 parts of accelerators, 0.5 to 1.5 parts of antioxidants, and 3 to 5 parts of dispersants; wherein sulfur is a vulcanizing agent and zinc oxide is a vulcanization activator. Among them, the accelerator is one or more of accelerator M, accelerator D, or accelerator PX, etc.; the antioxidant is one or more of antioxidant 4020, antioxidant 264, or antioxidant 2246, etc.; the dispersant is dispersant NNO. The components of the mixing aid are stirred and dispersed by a high-speed disperser, and then placed in a high-speed ball mill or roller mill for grinding for 5 to 6 hours.
[0013] In the present invention, the method for preparing the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry comprises the following steps:
[0014] 1) According to the raw materials and their mass parts, prepare 100 parts of monodisperse nano calcium carbonate filter cake, 0.2-2 parts of calcium carbonate surface capping agent, 0.5-1 parts of calcium ion complexing agent, 5-10 parts of potassium hydroxide solution, and 180-200 parts of deionized water;
[0015] 2) Place the monodisperse calcium carbonate filter cake in a portion of water (the weight of this portion of water is 1 to 1.5 times the weight of the monodisperse calcium carbonate filter cake) at a temperature of 5 to 30°C and stir and disperse it, and disperse it in a high-speed disperser at a linear speed of 80 to 120 m / min for 15 to 40 minutes;
[0016] 3) After the stirring in step 2) is completed, the remaining amount of water is added and the mixture is dispersed in a high-speed disperser at a linear speed of 80 to 120 m / min for 15 to 30 min;
[0017] 4) After the stirring of step 3) is completed, add a calcium carbonate surface capping agent, a calcium ion complexing agent and a potassium hydroxide solution, and disperse in a high-speed disperser at a linear speed of 80 to 120 m / min for 5 to 10 minutes to obtain the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry. The ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry is in a slurry state. After centrifugation, the supernatant is taken, the calcium ion concentration therein is determined, and the calcium ion concentration is used as the calcium ion activity data. The calcium ion activity in the monodisperse nano-calcium carbonate slurry is extremely low, less than 0.05 mmol / L, and there is no risk of flocculation when added to the nitrile latex emulsion.
[0018] The method for preparing a monodisperse nano calcium carbonate slurry with ultra-low calcium ion activity performs surface capping on calcium carbonate particles to passivate the surface of the calcium carbonate particles, thereby preventing calcium ions on the surface of the calcium carbonate from being dissolved in subsequent processing; further reduces the activity of calcium ions by adding a calcium ion complexing agent into the slurry, thereby ensuring that the slurry as a whole has ultra-low calcium ion activity; and further ensures the process stability for using the slurry in the production of latex products by adding a potassium hydroxide solution into the slurry.
[0019] Furthermore, in step 1), the amount of deionized water is preferably 187 to 194 parts.
[0020] Furthermore, in step 2), the mixture is stirred and dispersed in a high-speed disperser at a linear speed of 80 to 120 m / min for 15 to 40 min; in step 3), the mixture is stirred and dispersed in a high-speed disperser at a linear speed of 80 to 120 m / min for 15 to 30 min; in step 4), the mixture is stirred and dispersed in a high-speed disperser at a linear speed of 80 to 120 m / min for 5 to 10 min.
[0021] Furthermore, the method for preparing the monodisperse nano calcium carbonate filter cake comprises the following steps:
[0022] S1. A process including calcination, digestion, aging, impurity removal and carbonization is used to prepare calcium carbonate cooked pulp. The calcination process is as follows: limestone with uniform grain size and harmful heavy metal content less than 400ppm is selected as raw material, and calcined to obtain quicklime, and the activity of quicklime is in the range of 250-300mL; the digestion process is as follows: the quicklime obtained by the above calcination is digested in hot water at 50-90°C to obtain lime milk; the aging and impurity removal process is as follows: the lime milk is aged for 24-48h, and refined raw pulp is obtained after filtering and impurity removal; the carbonization process is as follows: the refined raw pulp is added with water to adjust the solid content to 5%-8%, and then carbonized, the carbonization starting temperature is 10-25°C, the CO2 content is 20%-40%, and the pulp pH reaches 9.0-10.0, and then the carbonization is terminated to obtain calcium carbonate cooked pulp;
[0023] S2. Add inorganic salt crystal surface reconstructor and organic crystal surface reconstructor to the calcium carbonate slurry obtained in S1, and then slurry the slurry under ultrasonic conditions (power density 100-300W / 1000cm 3 ) and heat at 120-140° C. for 1-4 hours to obtain a monodisperse calcium carbonate suspension having both finer particle size and smaller surface energy;
[0024] S3. The monodisperse calcium carbonate suspension obtained in S2 is subjected to secondary carbonization to make its pH value between 7.0 and 7.3, thereby obtaining a carbonized neutral monodisperse calcium carbonate suspension; the secondary carbonization process is as follows: the calcium carbonate suspension obtained by reconstructing the grain surface is carbonized, the carbonization starting temperature is 10 to 25°C, the CO2 content is 20% to 40%, and the slurry is carbonized to a pH value between 7.0 and 7.3, and precise secondary carbonization control is adopted to avoid under-carbonization residual Ca(OH)2 or over-carbonization to form Ca(HCO3)2, thereby reducing the calcium ion concentration in the product;
[0025] S4. The carbonized neutral monodisperse calcium carbonate suspension obtained in S3 is dehydrated by pressure filtration to obtain a calcium carbonate filter cake, the moisture content of which is controlled to be no more than 40%, i.e., a monodisperse nano calcium carbonate filter cake. Pressure filtration and centrifugation can discharge excess water, which is beneficial to the processing and transportation of calcium carbonate, and also rapidly reduce other soluble ions present in the solution during the production process, achieving the effect of ultra-low ion activity.
[0026] The average particle size of the calcium carbonate particles in the monodisperse nano calcium carbonate filter cake prepared by the above method is 50-100 nm, in a monodisperse state, and its specific surface area is 19-25 m 2 / g, which can effectively inhibit agglomeration, thus facilitating dispersion in the emulsion of nitrile latex and ensuring that nitrile latex gloves still have excellent performance at a higher calcium carbonate addition amount.
[0027] Furthermore, the inorganic grain surface reconstruction agent is one or more of inorganic salts such as sodium silicate, sodium chloride, aluminum chloride, zinc sulfate, etc., and the amount used is 0.5% to 3% of the dry basis mass of calcium carbonate; the organic grain surface reconstruction agent is one or more of organic substances such as ethanol, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, disodium ethylenediaminetetraacetic acid, etc., and the amount used is 1% to 5% of the dry basis mass of calcium carbonate.
[0028] On the basis of the above, the present invention also provides a method for preparing nitrile latex gloves comprising the following steps:
[0029] (1) adding casein, a mixing aid, nanocellulose and a defoaming agent to butadiene-acrylonitrile latex according to the raw materials of the present invention and their weight fractions, stirring and dispersing the mixture uniformly to obtain a mixed emulsion;
[0030] (2) adding the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry to the mixed solution obtained in step (1), stirring evenly to obtain a mixed material;
[0031] (3) After cleaning the glove mold, preheat it to 60-70°C and immerse it in a coagulant for 5-10 seconds. After immersion, take out the glove mold, shake off the excess coagulant, and then put it into a 60-70°C oven for 4-6 minutes;
[0032] (4) dipping the glove mold obtained in step (3) into the mixture obtained in step (2) for a dipping time of 5 to 10 seconds, then taking out the glove mold and dripping off the excess mixture, and then placing it in a 60 to 70° C. oven for a drying time of 4 to 6 minutes;
[0033] (5) immersing the glove mold obtained in step (4) in warm water at about 45° C. for 10 to 20 seconds, then taking out the glove mold, shaking off excess water, and placing it in a 60 to 70° C. oven after curling for 4 to 6 minutes;
[0034] (6) Immersing the glove mold obtained in step (5) into a 2% to 10% polyurethane solution for a dipping time of 5 to 10 seconds, then taking out the glove mold, shaking off excess polyurethane solution, and subsequently placing the glove mold in an oven at 120 to 130° C. for a drying time of 7 to 8 minutes, and demolding to obtain a nitrile latex glove with a high nano-calcium carbonate filling content.
[0035] When preparing a monodisperse nano calcium carbonate filter cake, the present invention selects limestone with uniform grain size and harmful heavy metal content of less than 400ppm such as cadmium, lead, chromium, etc. as a raw material, then adopts a calcination temperature matching the grain size to obtain quicklime with moderate and uniform activity, and carbonizes it after digestion to obtain calcium carbonate slurry. Limestone with uniform grain size is used as a raw material for preparing a monodisperse nano calcium carbonate filter cake, and the lime activity can be adjusted through a limestone calcination process to avoid partial raw burning and partial overburning caused by porphyritic grains; lime with good uniformity and moderate activity is conducive to the control of the digestion reaction, and uniform lime milk with controllable properties is obtained, thereby realizing the control of the later carbonization process, so as to obtain calcium carbonate slurry with expected particle size and grain morphology; the content of harmful heavy metals such as cadmium, lead, chromium, etc. in quicklime is less than 400ppm, which can ensure that the content of harmful heavy metals in the prepared monodisperse nano calcium carbonate filter cake is less than 200ppm, and ensure the safety of nitrile latex gloves using it as a filler.
[0036] When preparing a monodisperse nano calcium carbonate filter cake, the present invention has a process step of reconstructing the surface of the grains after carbonization is completed. The process is to add an inorganic surface reconstruction agent and an organic surface reconstruction agent and keep the temperature at a certain temperature under ultrasonic assistance conditions to promote the reconstruction of the grain surface, make the crystal more complete, and make the particle surface smoother, thereby reducing the surface energy, which is conducive to dispersion. The role of the inorganic surface reconstruction agent is to promote crystal development, repair defects, and make the crystal more complete; the role of the organic surface reconstruction agent is to adjust the surface potential of the particles, control the mutual repulsion of the grains in water, and avoid adhesion during the crystal repair process; ultrasonic assistance can improve the dispersibility of calcium carbonate particles. The present invention controls the average particle size of calcium carbonate particles to 50-100nm by controlling the temperature, time and ultrasonic power of the grain surface reconstruction, and is in a highly monodisperse state. This form of calcium carbonate particles enables it to play an excellent reinforcing effect as a filler for nitrile latex gloves.
[0037] In the present invention, the ultra-low calcium ion activity monodisperse nano calcium carbonate slurry uses monodisperse calcium carbonate filter cake as the main raw material, disperses the filter cake in deionized water, and adds calcium carbonate surface capping agent and calcium ion complexing agent, as well as stabilizer potassium hydroxide solution, so as to obtain the ultra-low calcium ion activity monodisperse nano calcium carbonate slurry product for nitrile latex gloves of the present invention. First, the monodisperse calcium carbonate filter cake maintains no more than 40% of water, and maintains a water film and a double electric layer structure between the calcium carbonate solid particles, which can ensure that the surface state and repulsion of the calcium carbonate particles are not destroyed to the greatest extent, and no agglomeration occurs, so that it can be quickly redispersed in the aqueous solution when the dispersion machine assists in stirring, and maintains stable suspension. More importantly, by performing surface capping on the calcium carbonate particles, the particle surface is passivated, the calcium ions on the surface of the calcium carbonate are prevented from dissolving in the subsequent processing, and the calcium ion activity is reduced by adding a calcium ion complexing agent in the slurry, so as to ensure that the overall calcium ion activity is ultra-low, which is lower than 0.05mmol / L.
[0038] The nitrile latex gloves with high filling amount of nano calcium carbonate prepared by the technical solution of the present invention have excellent water phase dispersibility and ultra-low calcium ion activity in the filler (i.e., ultra-low calcium ion activity monodisperse nano calcium carbonate slurry), which ensures the stability of the production process, and its strict particle size control and good dispersibility in nitrile latex ensure its excellent reinforcement effect on nitrile latex gloves. Compared with latex gloves products with the same mass fraction of water-ground light calcium, the tensile strength of the nitrile latex gloves prepared by the present invention is increased by 30%, and the elongation at break is increased by 20%; compared with the water-ground light calcium filler with the same mechanical properties, the formula cost of the nitrile latex gloves prepared by the present invention is lower, and the cost is reduced by 20%.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. The present invention makes monodisperse nano calcium carbonate into ultra-low calcium ion activity monodisperse nano calcium carbonate slurry, which is used as a filler for the nitrile latex gloves of the present invention, strictly controls the calcium ion concentration, and does not produce the risk of latex flocculation when added to the nitrile latex gloves, thereby preventing the stability of the nitrile product production process from being destroyed; and the ultra-low calcium ion activity monodisperse nano calcium carbonate slurry is a filler, which has good dispersibility in nitrile latex, and the particle size is finer than that of water-ground light calcium, and can play an excellent reinforcement effect when added to nitrile latex gloves, and obtains better mechanical properties, and the tensile strength of the latex products added with the same mass fraction of water-ground light calcium is increased by 30%, and the elongation at break is increased by 20%. Therefore, the present invention effectively makes up for the problems of low addition amount of inorganic filler, poor reinforcement effect, poor stability of production process, etc. in the prior art, and provides a new way to solve the contradiction between cost and performance for nitrile latex gloves.
[0041] 2. The formula cost of the nano calcium carbonate high-filling nitrile latex gloves of the present invention is low. Compared with adding water-ground light calcium as a filler to achieve the same mechanical properties, the formula cost is reduced by 20%. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a scanning electron microscope photograph of the monodisperse nano-calcium carbonate prepared in Example 1;
[0043] Figure 2 This is a scanning electron microscope photograph of the monodisperse nano-calcium carbonate prepared in Example 2;
[0044] Figure 3 This is a scanning electron microscope photograph of the monodisperse nano-calcium carbonate prepared in Example 3;
[0045] Figure 4 This is a scanning electron microscope photograph of the calcium carbonate prepared in Comparative Example 1;
[0046] Figure 5 This is a scanning electron microscope photograph of the calcium carbonate prepared in Comparative Example 2. Specific implementation methods
[0048] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0049] In the present invention, the calcium carbonate surface capping agent, calcium ion complexing agent, organic crystal reconstructing agent, and inorganic crystal reconstructing agent are all commercially available analytically pure reagents. In the following examples, sodium polyacrylate is in liquid state, with an effective component greater than 40% and a molecular weight of 3000; the polyethylene glycol model is PEG-400; and the polyvinyl pyrrolidone model is PVP K30.
[0050] In the following embodiments, the nitrile latex is a high-nitrile nitrile latex purchased from Zhejiang Tianchen Rubber Industry Co., Ltd., and the model is medical nitrile latex TC-N135R.
[0051] In the following examples, casein is commercially available casein purchased from Gansu Hualing Dairy Co., Ltd., model: edible casein.
[0052] In the following examples, the cellulose is hydroxymethyl cellulose, and its CAS number is 9004-32-4.
[0053] In the following examples, the defoaming agent is an organosilicon defoaming agent purchased from Shanghai Sangjing Chemical Co., Ltd., model DF-963.
[0054] In the following embodiments, the mixed auxiliary agent is composed of 30 parts of sulfur, 20 parts of zinc oxide, 10 parts of accelerator D, 1 part of antioxidant 4020, 4 parts of dispersant NNO and 100 parts of deionized water by mass; the above-mentioned auxiliary agents are stirred and dispersed by a high-speed disperser and then ground in a high-speed ball mill or roller mill for 4 hours. Among them, sulfur is purchased from Linyi Houpu Chemical Co., Ltd., model: rubber sulfur powder; zinc oxide is purchased from Weifang Aolong Zinc Industry Co., Ltd., model: zinc oxide for rubber and plastic; accelerator D is diphenylguanidine, CAS No. 102-06-7; antioxidant 4020 is N-(1.3 dimethylbutyl)-N'-phenyl-p-phenylenediamine, CAS No. 793-24-8; dispersant NNO is sodium methylenebisnaphthalenesulfonate, CAS No. 36290-04-7.
[0055] Example 1
[0056] (1) This embodiment first provides a monodisperse nano calcium carbonate filter cake, and the specific steps of its preparation method are as follows:
[0057] S1. Prepare calcium carbonate slurry by calcination, digestion, carbonization and other processes. The calcination process is as follows: select limestone with a grain size of 0.2-0.5 mm and a content of harmful heavy metals such as cadmium, lead, chromium and less than 400 ppm as raw material, adopt a calcination temperature of 900°C, calcine for 2 hours, and obtain quicklime with ideal activity; the digestion process is as follows: digest the quicklime obtained by the calcination with water at 90°C to obtain lime milk; the aging and impurity removal process is as follows: filter and remove impurities after aging the lime milk for 24 hours to obtain refined raw slurry; the carbonization process is as follows: add water to the refined raw slurry obtained by digestion to adjust the solid content to 5%, and then carbonize it. The starting temperature of carbonization is 25°C, the CO2 content is 33%, and the slurry pH reaches 9.0-10.0. Then, carbonization is terminated to obtain calcium carbonate slurry;
[0058] S2. Add 0.5% aluminum chloride, 0.5% ethanol, 1% polyethylene glycol, 0.5% polyvinyl pyrrolidone and 2% sodium dodecylbenzene sulfonate to the calcium carbonate slurry obtained in S1, and mix them under an ultrasonic power density of 300W / 1000cm 3 Under the above conditions, the dispersion and reconstitution were carried out at 120°C for 4 h to obtain a monodisperse calcium carbonate suspension;
[0059] S3. The calcium carbonate suspension obtained in S2 was subjected to secondary carbonization, the carbonization starting temperature was 25 ° C, the CO2 content was 33%, and the slurry was carbonized to a pH value between 7.0 and 7.3 to obtain a carbonized neutral monodisperse calcium carbonate suspension;
[0060] S4. The calcium carbonate slurry obtained in S3 is dehydrated by filter pressing to obtain a calcium carbonate filter cake, the moisture content of the filter cake is 40%, that is, a monodisperse calcium carbonate filter cake. At this time, take an appropriate amount of filter cake and dry it at 105°C, and then test and analyze its composition, specific surface area, micromorphology and particle size. The composition and specific surface area tests are carried out according to the "Calcium Carbonate Analysis Method" (GB / T 19281-2014) standard, and the micromorphology and particle size tests are carried out according to the "Nano Calcium Carbonate" (GB / T 19590-2023) standard. The contents of harmful impurities such as cadmium, lead, barium, mercury, and arsenic in the obtained monodisperse nano calcium carbonate filter cake are all less than 0.0002%, and the total content of harmful impurities is less than 200ppm; the specific surface area is about 19.02m 2 / g; from the scanning electron microscope photo (see Figure 1 ) It can be clearly seen that the average particle size of the calcium carbonate particles in the obtained monodisperse nano-calcium carbonate filter cake is about 100nm, the particles larger than 200nm account for less than 5%, the particles are cubic, the surface is flat and clean, and they are in a monodisperse state.
[0061] (2) On the basis of the above, this embodiment also provides a monodisperse nano-calcium carbonate slurry with ultra-low calcium ion activity, which is prepared from the following raw materials in the following mass proportions: 100 parts of monodisperse nano-calcium carbonate filter cake, 1 part of sodium polyacrylate, 1 part of 4A zeolite, 10 parts of 10wt% potassium hydroxide solution, and 188 parts of deionized water. The preparation process is as follows: according to the above raw materials and their mass proportions, 100 parts of monodisperse nano-calcium carbonate filter cake and 100 parts of deionized water are stirred for 15 minutes with a high-speed disperser at a stirring line speed of 120m / min; 88 parts of deionized water are added as the remainder, and the mixture is stirred for 15 minutes with a high-speed disperser at a stirring line speed of 120m / min; sodium polyacrylate, 4A zeolite and 10wt% potassium hydroxide solution are added according to the above formula, and the mixture is stirred for 5 minutes with a high-speed disperser at a stirring line speed of 120m / min, so as to obtain the monodisperse nano-calcium carbonate slurry with ultra-low calcium ion activity used in this embodiment. At this time, take an appropriate amount of monodisperse nano calcium carbonate slurry, centrifuge it at 5000r / min using a high-speed centrifuge to obtain the supernatant, and use a calcium ion titrator to measure the calcium ion concentration of the supernatant. The calcium ion concentration is 0.044mmol / L, which is the calcium ion activity. Note: The concentration of free calcium ions dispersed in calcium carbonate in aqueous solution is the calcium ion activity. When using the electrode determination method to test, taking the supernatant for testing can ensure the accuracy of the calcium ion electrode.
[0062] (3) On the basis of the above, this embodiment also provides a nitrile latex glove with a high filling amount of nano-calcium carbonate, which is made of the following raw materials in the following weight ratio: 100 parts of nitrile latex, 2.5 parts of casein, 3.0 parts of mixing aid, 0.9 parts of cellulose, 25 parts of ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry, and 1.5 parts of defoaming agent.
[0063] The preparation method of the nitrile latex gloves with high nano calcium carbonate filling amount described in this embodiment is as follows:
[0064] (1) adding casein, a mixing aid, cellulose and a defoaming agent to butadiene-acrylonitrile latex according to the above raw materials and their weight fractions, stirring and dispersing for 0.5 h to obtain a mixed solution;
[0065] (2) adding the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry to the mixed solution obtained in step (1), stirring for 0.5 h to obtain a uniformly mixed mixture;
[0066] (3) After cleaning the glove mold, preheat it to 70°C and immerse it in the coagulant for 5 seconds. After immersion, take out the glove mold, shake off the excess coagulant, and then put it into a 65°C oven for 5 minutes;
[0067] (4) dipping the glove mold obtained in step (3) into the mixture obtained in step (2) for a dipping time of 5 to 10 seconds, taking out the glove mold to allow excess mixture emulsion to drip off, and then placing it in a 65° C. oven for a drying time of 5 minutes;
[0068] (5) immersing the glove mold obtained in step (4) in 45° C. warm water for 10 seconds, taking out the glove mold, shaking off excess water, and placing it in a 65° C. oven after curling for 5 minutes;
[0069] (6) immersing the glove mold of step (5) into a 2 wt % polyurethane solution for 10 s, taking out the glove mold, shaking off the excess polyurethane solution, and then putting it into an oven and setting the oven temperature to 125° C., and controlling the vulcanization time (i.e., drying time) to 7.5 min;
[0070] (7) After the vulcanization is completed, demoulding is performed to obtain nitrile latex gloves with a high filling amount of nano calcium carbonate.
[0071] Example 2
[0072] (1) This embodiment first provides a monodisperse nano-calcium carbonate filter cake, and its preparation method is different from that of Example 1 in that: the digestion temperature in step S1 is 80°C, the aging time is 30h, the solid content of the refined raw pulp in the carbonization process is 8%, the carbonization starting temperature is 20°C, and the CO2 content is 35%; in step S2, 1.5% of sodium chloride, 1.5% of sodium silicate, 0.5% of polyvinyl alcohol and 0.5% of sodium dodecyl sulfate are added in the process of grain surface reconstruction by dry basis weight of calcium carbonate, and the mixture is heated to 400°C under an ultrasonic power density of 200W / 1000cm 3 Under the conditions, keep warm at 130℃ for 3h.
[0073] The same test method as in Example 1 was used to test and analyze the composition, specific surface area, microscopic morphology and particle size of the monodisperse calcium carbonate filter cake obtained in this example. The contents of harmful impurities such as cadmium, lead, barium, mercury and arsenic in the monodisperse nano calcium carbonate obtained were all less than 0.0002%, and the total content of harmful impurities was less than 200 ppm; the specific surface area was 20.15 m 2 / g; From the SEM photos (see Figure 2 ) It can be clearly seen that the average particle size of the obtained monodisperse nano-calcium carbonate particles is about 70nm, the particles are cubic and the surface is smooth and clean.
[0074] (2) On the basis of the above, this embodiment also provides an ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry, which is prepared from the following raw materials in the following weight ratio: 100 parts of monodisperse calcium carbonate filter cake, 2 parts of sodium methylene bisnaphthalene sulfonate, 0.5 parts of disodium ethylenediaminetetraacetate, 8 parts of 10wt% potassium hydroxide solution, and 189.5 parts of deionized water. The preparation process is as follows: according to the above raw materials and their mass fractions, 100 parts of monodisperse calcium carbonate filter cakes are added to 150 parts of deionized water, and stirred for 25 minutes by a high-speed disperser at a stirring line speed of 100 m / min; the remaining 39.5 parts of deionized water are added, and the mixture is continuously stirred for 15 minutes by a high-speed disperser at a stirring line speed of 100 m / min; then sodium methylenebisnaphthalene sulfonate, disodium ethylenediaminetetraacetate and 10wt% potassium hydroxide solution are added according to the above formula, and the mixture is continuously stirred for 8 minutes by a high-speed disperser at a stirring line speed of 100 m / min, so as to obtain the ultra-low calcium ion activity monodisperse nano calcium carbonate slurry for nitrile latex gloves described in this embodiment, wherein the calcium ion activity is 0.015 mmol / L.
[0075] (3) On the basis of the above, this embodiment also provides a nitrile latex glove with a high filling amount of nano-calcium carbonate, which is prepared from the following raw materials in the following weight ratio: 100 parts of nitrile latex, 4.8 parts of casein, 3.4 parts of mixing aid, 0.6 parts of cellulose, 15 parts of ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry, and 1.0 part of defoaming agent.
[0076] The preparation method of the nano calcium carbonate high-filling nitrile latex gloves described in this embodiment is as follows:
[0077] (1) adding casein, a mixing aid, cellulose and a defoaming agent to butadiene-acrylonitrile latex according to the above raw materials and their weight fractions, stirring and dispersing for 0.5 h to obtain a mixed solution;
[0078] (2) adding the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry to the mixed solution obtained in step (1), stirring for 0.5 h to obtain a uniformly mixed mixture;
[0079] (3) After cleaning the glove mold, preheat it to 60°C and immerse it in the coagulant for 10 seconds. After immersion, take out the glove mold, shake off the excess coagulant, and then put it into a 65°C oven for 5 minutes;
[0080] (4) dipping the glove mold of step (3) into the mixture for a dipping time of 5 to 10 seconds, taking out the glove mold to allow excess emulsion to drip off, and then placing it in a 65° C. oven for a drying time of 5 minutes;
[0081] (5) immersing the glove mold of step (4) in 45° C. warm water for 10 to 20 seconds, taking out the glove mold, shaking off the water, curling the glove mold and placing it in a 65° C. oven for 5 minutes;
[0082] (6) Immerse the glove mold of step (5) in a 10% polyurethane solution for 5 seconds, take out the glove mold, shake off the excess coating, and then put it into an oven and set the oven temperature to 125° C., and control the vulcanization time to 7.5 minutes.
[0083] (7) After the vulcanization is completed, the nano-calcium carbonate high-filling nitrile latex gloves are demoulded.
[0084] Example 3
[0085] (1) This embodiment first provides a monodisperse nano-calcium carbonate filter cake, and its preparation method is different from that of Example 1 in that: the digestion temperature in step S1 is 50°C, the aging time is 48h, the solid content of the refined raw pulp in the carbonization process is 10%, the carbonization starting temperature is 10°C, and the CO2 content is 40%; in step S2, 0.5% of sodium chloride, 0.5% of sodium silicate, 1% of zinc sulfate and 2% of hexadecyltrimethylammonium bromide are added to the surface reconstruction of the calcium carbonate dry basis during the ultrasonic power density of 100W / 1000cm 3 Under the conditions, keep warm at 140℃ for 1h.
[0086] The composition, specific surface area, microscopic morphology and particle size of the monodisperse calcium carbonate filter cake obtained in this embodiment were tested and analyzed by the same test method as in Example 1. The contents of harmful impurities such as cadmium, lead, barium, mercury and arsenic in the monodisperse nano calcium carbonate were all less than 0.0002%, and the total content of harmful impurities was less than 200 ppm; the specific surface area was 24.79 m 2 / g; From the SEM photos (see Figure 3 ) It can be clearly seen that the average particle size of the obtained monodisperse nano-calcium carbonate particles is about 55nm, the particles are nearly spherical, and the surface is smooth and clean.
[0087] (2) On the basis of the above, this embodiment also provides a monodisperse nano-calcium carbonate slurry with ultra-low calcium ion activity, which is prepared from the following raw materials in the following mass proportions: 100 parts of monodisperse nano-calcium carbonate filter cake, 0.2 parts of sodium hexametaphosphate, 0.5 parts of sodium citrate, 5 parts of 10% potassium hydroxide solution and 194 parts of deionized water; the preparation process is as follows: according to the above raw materials and their mass proportions, 100 parts of monodisperse calcium carbonate filter cake and 120 parts of deionized water are mixed with a high-speed disperser at a stirring speed of 80m / min. The mixture was stirred at a speed of 80 m / min for 40 min; 74 parts of deionized water were added as the remainder, and the mixture was stirred at a stirring speed of 80 m / min for 30 min using a high-speed disperser; sodium hexametaphosphate, sodium citrate and 10 wt % potassium hydroxide solution were added according to the above formula, and the mixture was stirred at a stirring speed of 80 m / min for 10 min using a high-speed disperser to obtain the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry for nitrile latex gloves described in this embodiment, and the calcium ion activity was 0.023 mmol / L.
[0088] (3) On the basis of the above, this embodiment also provides a nitrile latex glove with a high filling amount of nano-calcium carbonate, which is prepared from the following raw materials in the following weight ratio: 100 parts of nitrile latex, 0.5 parts of casein, 2.3 parts of mixing aid, 1.2 parts of cellulose, 5 parts of ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry, and 0.1 parts of defoaming agent.
[0089] The preparation method of the nano calcium carbonate high-filling nitrile latex gloves described in this embodiment is as follows:
[0090] (1) adding casein, a mixing aid, cellulose and a defoaming agent to butadiene-acrylonitrile latex according to the above raw materials and their weight fractions, stirring and dispersing for 0.5 h to obtain a mixed solution;
[0091] (2) adding the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry to the mixed solution obtained in step (1), stirring for 0.5 h to obtain a uniformly mixed mixture;
[0092] (3) After cleaning the glove mold, preheat it to 65°C and immerse it in the coagulant for 8 seconds. After immersion, take out the glove mold, shake off the excess coagulant, and then put it into a 65°C oven for 5 minutes;
[0093] (4) dipping the glove mold of step (3) into the mixture for a dipping time of 5 to 10 seconds, taking out the glove mold to allow excess emulsion to drip off, and then placing it in a 65° C. oven for a drying time of 5 minutes;
[0094] (5) immersing the glove mold of step (4) in 45° C. warm water for 15 seconds, taking out the glove mold, shaking off the water, curling the glove mold and placing it in a 65° C. oven for 5 minutes;
[0095] (6) Immersing the glove mold of step (5) into a 5 wt % polyurethane solution for 8 seconds, taking out the glove mold, shaking off the excess coating, and then putting it into an oven and setting the oven temperature to 125° C., and controlling the vulcanization time to 7.5 minutes.
[0096] (7) After the vulcanization is completed, the nano-calcium carbonate high-filling nitrile latex gloves are demoulded.
[0097] Example 4
[0098] (1) This embodiment first provides a monodisperse nano calcium carbonate filter cake, and its preparation method is the same as that of Example 2.
[0099] (2) On the basis of the above, this embodiment also provides a monodisperse nano-calcium carbonate slurry with ultra-low calcium ion activity, which is prepared from the following raw materials in the following mass proportions: 100 parts of monodisperse nano-calcium carbonate filter cake, 1.2 parts of sodium methylene bis-naphthalene sulfonate, 0.8 parts of 4A molecular sieve, 6 parts of 10% potassium hydroxide solution and 192 parts of deionized water; its preparation process is as follows: according to the above raw materials and their mass proportions, 100 parts of monodisperse calcium carbonate filter cake and 130 parts of deionized water are mixed with a high-speed disperser at a stirring speed of 110 m / min. The mixture was stirred at a stirring speed of 110 m / min for 6 min, and the mixture was stirred at a stirring speed of 110 m / min for 20 min by a high-speed disperser. The mixture was then added with sodium methylenebisnaphthalenesulfonate, 4A molecular sieve and 10 wt % potassium hydroxide solution according to the above formula, and the mixture was stirred at a stirring speed of 110 m / min for 6 min by a high-speed disperser to obtain the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry for nitrile latex gloves described in this embodiment, wherein the calcium ion activity is 0.002 mmol / L.
[0100] (3) On the basis of the above, this embodiment also provides a nitrile latex glove with a high filling amount of nano-calcium carbonate, which is prepared from the following raw materials in the following weight ratio: 100 parts of nitrile latex, 3 parts of casein, 2.6 parts of mixing aid, 1.1 parts of cellulose, 10 parts of ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry, and 0.7 parts of defoaming agent.
[0101] The preparation method of the nano calcium carbonate high-filling nitrile latex gloves described in this embodiment is as follows:
[0102] (1) adding casein, a mixing aid, cellulose and a defoaming agent to butadiene-acrylonitrile latex according to the above raw materials and their weight fractions, stirring and dispersing for 0.5 h to obtain a mixed solution;
[0103] (2) adding the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry to the mixed solution obtained in step (1), stirring for 0.5 h to obtain a uniformly mixed mixture;
[0104] (3) After cleaning the glove mold, preheat it to 70°C and immerse it in the coagulant for 5 seconds. After immersion, take out the glove mold, shake off the excess coagulant, and then put it into a 65°C oven for 5 minutes;
[0105] (4) dipping the glove mold of step (3) into the mixture for a dipping time of 5 to 10 seconds, taking out the glove mold to allow excess emulsion to drip off, and then placing it in a 65° C. oven for a drying time of 5 minutes;
[0106] (5) immersing the glove mold of step (4) in 45° C. warm water for 10 seconds, taking out the glove mold, shaking off the water, curling the glove mold and placing it in a 65° C. oven for 5 minutes;
[0107] (6) Immersing the glove mold of step (5) into an 8 wt % polyurethane solution for 7 seconds, taking out the glove mold, shaking off the excess coating, and then placing it into an oven and setting the oven temperature to 125° C., and controlling the vulcanization time to 7.5 minutes.
[0108] (7) After the vulcanization is completed, the nano-calcium carbonate high-filling nitrile latex gloves are demoulded.
[0109] Comparative Example 1
[0110] The difference between Comparative Example 1 and Example 1 is that an equal amount of commercially available water-ground light calcium slurry is used to replace the ultra-low calcium ion activity monodisperse nano calcium carbonate slurry for preparing nitrile latex gloves. The rest is the same as Example 1. The nitrile latex gloves finally prepared in Comparative Example 1 are hard and have poor mechanical properties.
[0111] Comparative Example 2
[0112] The difference between Comparative Example 2 and Example 1 is that during the preparation of the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry, the 10 wt % potassium hydroxide solution is replaced with an equal amount of deionized water, and then the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry is used to prepare nitrile latex gloves. The rest is the same as Example 1.
[0113] In Comparative Example 2, because 10 wt % potassium hydroxide solution was not added, the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry was added to the nitrile latex, and the mixture was stirred and evenly mixed and then left to stand for 1 hour, the latex flocculated and qualified nitrile latex gloves could not be produced.
[0114] Comparative Example 3
[0115] The difference between Comparative Example 3 and Example 1 is that: instead of using a monodisperse nano-calcium carbonate filter cake, the neutral monodisperse calcium carbonate suspension obtained after secondary carbonization is directly used to prepare an ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry, and then the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry is used to prepare nitrile latex gloves. The other steps are the same as those in Example 1.
[0116] In Comparative Example 3, because the soluble ions in the slurry were not removed by filtration, the slurry was added to the nitrile latex, stirred and mixed evenly, and then allowed to stand for 2 hours to cause latex flocculation, and qualified nitrile latex gloves could not be produced.
[0117] Comparative Example 4
[0118] Comparative Example 4 has the same formula as Example 1, except that the preparation method of the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry is different from that of Example 1. The preparation process is as follows: 100 parts of monodisperse nano-calcium carbonate filter cakes are directly added to 188 parts of deionized water, stirred for 30 minutes with a high-speed disperser at a stirring line speed of 120m / min, and after stirring evenly, 1 part of sodium polyacrylate, 1 part of 4A zeolite and 10 parts of 10wt% potassium hydroxide solution are added according to the ingredient relationship, and stirring is continued at a stirring line speed of 120m / min for 5 minutes to obtain the ultra-low calcium ion activity monodisperse calcium carbonate slurry used in this comparative example 4; and then the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry is used to prepare nitrile latex gloves. Others are the same as Example 1.
[0119] Comparative Example 4 does not have a high-concentration stirring step, resulting in poor dispersion of calcium carbonate. When calcium carbonate is added to nitrile latex, the resulting nitrile latex glove product has poor mechanical properties.
[0120] Comparative Example 5
[0121] The only difference between Comparative Example 5 and Example 3 is that no inorganic crystal surface reconstructor is added in the preparation method of the monodisperse nano calcium carbonate filter cake, and the microscopic morphology of the obtained product is shown in FIG. Figure 4 , and then, used to prepare ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry, and further prepared nitrile latex gloves.
[0122] In Comparative Example 5, because no inorganic grain surface reconstructor was added, the surface of the calcium carbonate grains was rough, connections were formed between the particles, and the dispersion between the particles was relatively poor. When it was added to nitrile latex, the calcium carbonate particles had poor dispersion in the latex, and the prepared nitrile latex gloves had white spots on the appearance and poor mechanical properties.
[0123] Comparative Example 6
[0124] The only difference between Comparative Example 6 and Example 3 is that no organic crystal surface reconstruction agent is added in the preparation method of the monodisperse nano calcium carbonate filter cake, and the microscopic morphology of the obtained product is shown in FIG. Figure 5 , and then, used to prepare ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry, and further prepared nitrile latex gloves.
[0125] In Comparative Example 6, since no organic crystal surface reconstructor was added, the surface of the calcium carbonate crystals was clean, but the dispersion between the particles was still relatively poor, and connections were formed between the particles. When it was added to nitrile latex, the calcium carbonate particles had poor dispersion in the latex, and the prepared nitrile latex gloves had white spots on the appearance and poor mechanical properties.
[0126] Comparative Example 7
[0127] The only difference between Comparative Example 7 and Example 3 is that when preparing the monodisperse nano-calcium carbonate slurry, no surface capping agent sodium hexametaphosphate is added, and the calcium ion activity of the obtained monodisperse nano-calcium carbonate slurry is 0.52 mmol / L; and then the monodisperse nano-calcium carbonate slurry is used to prepare nitrile latex gloves.
[0128] In Comparative Example 7, when preparing the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry, because no calcium carbonate surface capping agent was added, the calcium ion activity was relatively high. When it was added to the nitrile latex and stirred for 10 minutes, the latex flocculation occurred and qualified nitrile latex gloves could not be produced.
[0129] Comparative Example 8
[0130] The only difference between Comparative Example 8 and Example 4 is that when preparing the monodisperse nano-calcium carbonate slurry, no calcium ion complexing agent 4A molecular sieve is added, and the calcium ion activity of the obtained monodisperse nano-calcium carbonate slurry is 1.08 mmol / L; and then the monodisperse nano-calcium carbonate slurry is used to prepare nitrile latex gloves.
[0131] In Comparative Example 8, since no calcium ion complexing agent was added, the calcium ion activity was high. When it was added to the nitrile latex, latex flocculation occurred after stirring and mixing for 5 minutes, and qualified nitrile latex gloves could not be produced.
[0132] The above-mentioned examples, comparative examples and nitrile latex gloves prepared by adding commercially available water-ground light calcium were tested for performance, 10 samples were taken from each group, the nitrile latex gloves were M-type, weighing about 7g / piece, and the tensile properties of the nitrile latex gloves were tested according to the requirements of the American standard ASTMD3577-19. Among them, comparative examples 3, 7 and 8 could not prepare glove samples due to latex flocculation, so no sample-related performance evaluation was performed.
[0133] Table 1 Properties of nitrile latex gloves prepared in various embodiments and comparative examples
[0134]
[0135]
[0136] Note: The calcium carbonate slurry represents the ultra-low calcium ion activity monodisperse nano calcium carbonate slurry prepared in the example, or the calcium carbonate slurry prepared in the comparative example, or the commercially available water-ground light calcium.
[0137] It can be seen from Table 1 that the tensile strength of the nitrile latex gloves prepared in the embodiment of the present invention before aging is 22-29 MPa, and the elongation is 664%-790%; the tensile strength after aging is 21-28 MPa, and the elongation is 662%-787%. Among them, when the addition amount of calcium carbonate is 5phr, compared with the addition of commercially available water-ground light calcium products, the tensile strength and elongation of the nitrile latex gloves prepared in Example 3 before and after aging are much higher than the ASTM D3577-19 standard requirements (in this standard, before aging: minimum tensile strength 17MPa, minimum elongation 650%; after aging: minimum tensile strength 12MPa, minimum elongation 490%); and the nitrile latex gloves prepared by adding commercially available water-ground light calcium products, although the tensile strength can be maintained at a good level, its elongation is very close to the minimum elongation required by the standard, which can clearly show that the nitrile latex gloves prepared by adding commercially available water-ground light calcium products have poor softness, which is also the direct reason why the addition amount of commercially available water-ground light calcium products in the production formula of nitrile latex gloves cannot be increased. As the amount of the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry prepared by the present invention is further increased (see Example 4 and Example 2, the amount of addition is 10phr and 15phr, respectively), the tensile strength and elongation are still much higher than the ASTM D3577-19 standard requirements. When it is further increased to 25phr (see Example 1), the elongation of the nitrile latex gloves decreases significantly, but still meets the ASTM D3577-19 standard requirements, and is substantially equal to the mechanical properties of the nitrile latex gloves added with 5phr of commercially available water-milled light calcium products.
[0138] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A monodisperse nano-calcium carbonate slurry with ultra-low calcium ion activity, characterized in that: The raw material composition includes 100 parts of monodisperse nano calcium carbonate filter cake, 0.2-2 parts of calcium carbonate surface capping agent, 0.5-1 parts of calcium ion complexing agent, 5-10 parts of potassium hydroxide solution and 180-200 parts of water by weight; wherein the concentration of potassium hydroxide solution is 5-15wt%; The water content of the monodisperse nano calcium carbonate filter cake is not more than 40%, the average particle size of the calcium carbonate particles is between 50 and 100 nm, and the specific surface area of the powder is between 19 and 25 m 2 / g, particles larger than 200nm are less than 5%, in a monodisperse state; The calcium ion activity of the monodisperse nano-calcium carbonate slurry is lower than 0.05 mmol / L based on the calcium ion concentration in the supernatant.
2. The ultra-low calcium ion activity monodisperse nano calcium carbonate slurry according to claim 1, characterized in that: The calcium carbonate surface capping agent includes one or more of sodium hexametaphosphate, sodium polyacrylate, and sodium methylene bisnaphthalene sulfonate; the calcium ion complexing agent includes one or more of sodium citrate, aminotri(methylenephosphonic acid), disodium ethylenediaminetetraacetate, molecular sieves, zeolite, and montmorillonite.
3. The ultra-low calcium ion activity monodisperse nano calcium carbonate slurry according to claim 1, characterized in that: The method for preparing the monodisperse nano calcium carbonate filter cake comprises the following steps: S1. A process including calcination, digestion, aging, impurity removal and carbonization is used to prepare calcium carbonate slurry. The calcination process is as follows: limestone with uniform grain size and harmful heavy metal content less than 400ppm is selected as raw material, and calcined to obtain quicklime, and the activity of quicklime is in the range of 250-300mL; the digestion process is as follows: the quicklime obtained by the above calcination is digested in hot water at 50-90°C to obtain lime milk; the aging and impurity removal process is as follows: the lime milk is aged for 24-48h, and refined raw slurry is obtained after filtering and impurity removal; the carbonization process is as follows: water is added to the refined raw slurry to adjust the solid content to 5%-8%, and then carbon dioxide is introduced for carbonization, the carbonization starting temperature is 10-25°C, the CO2 content is 20%-40%, and the slurry pH reaches 9.0-10.0, and then the carbonization is terminated to obtain calcium carbonate slurry; S2. adding an inorganic salt crystal surface reconstructor and an organic crystal surface reconstructor to the calcium carbonate slurry obtained in S1, and then keeping the mixture at 120 to 140° C. for 1 to 4 hours under ultrasonic conditions to obtain a monodisperse calcium carbonate suspension; S3. The monodisperse calcium carbonate suspension obtained in S2 is subjected to secondary carbonization, the secondary carbonization starting temperature is 10 to 25 ° C, the CO2 content is 20% to 40%, and the slurry is carbonized to a pH value between 7.0 and 7.3 to obtain a carbonized neutral monodisperse calcium carbonate suspension; S4. The carbonized neutral monodisperse calcium carbonate suspension obtained in S3 is filtered and dehydrated to obtain a calcium carbonate filter cake, wherein the moisture content of the filter cake is controlled to be no more than 40%, i.e., a monodisperse nano calcium carbonate filter cake.
4. The ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry according to claim 3, characterized in that: The inorganic grain surface reconstruction agent is one or more of sodium silicate, sodium chloride, aluminum chloride, and zinc sulfate, and the dosage is 0.5% to 3% of the dry basis mass of calcium carbonate; the organic grain surface reconstruction agent is one or more of ethanol, polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, and disodium ethylenediaminetetraacetate, and the dosage is 1% to 5% of the dry basis mass of calcium carbonate.
5. The method for preparing a monodisperse nano-calcium carbonate slurry with ultra-low calcium ion activity according to claim 1, 2 or 3, characterized in that: The steps include: 1) According to the raw materials and their mass parts, prepare 100 parts of monodisperse nano calcium carbonate filter cake, 0.2-2 parts of calcium carbonate surface capping agent, 0.5-1 parts of calcium ion complexing agent, 5-10 parts of potassium hydroxide solution, and 180-200 parts of deionized water; 2) placing the monodisperse calcium carbonate filter cake in a portion of water and stirring and dispersing the portion of water at a temperature of 5 to 30° C.; wherein the weight of the portion of water in this step is 1 to 1.5 times the weight of the monodisperse calcium carbonate filter cake; 3) After the stirring in step 2) is completed, add the remaining amount of water and continue to stir and disperse; 4) After the stirring in step 3) is completed, a calcium carbonate surface capping agent, a calcium ion complexing agent and a potassium hydroxide solution are added and stirred and dispersed to obtain the ultra-low calcium ion activity monodisperse nano calcium carbonate slurry.
6. The method for preparing a monodisperse nano-calcium carbonate slurry with ultra-low calcium ion activity according to claim 5, characterized in that: In step 2), the mixture is stirred and dispersed in a high-speed disperser at a linear speed of 80 to 120 m / min for 15 to 40 min; in step 3), the mixture is stirred and dispersed in a high-speed disperser at a linear speed of 80 to 120 m / min for 15 to 30 min; in step 4), the mixture is stirred and dispersed in a high-speed disperser at a linear speed of 80 to 120 m / min for 5 to 10 min.
7. A nitrile latex glove with a high filling amount of nano calcium carbonate, characterized in that: The raw materials include, by mass, 100 parts of nitrile latex, 0.5-4.8 parts of casein, 0.6-1.2 parts of cellulose, 5-25 parts of the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry according to claim 1, 2 or 3, 0.1-1.5 parts of defoaming agent and 2.3-3.4 parts of mixing aid; wherein the mixing aid is an aqueous solution including a vulcanizing agent, a vulcanization activator and an accelerator, a dispersant and an antioxidant.
8. The nitrile latex gloves with high nano-calcium carbonate filling according to claim 7, characterized in that: The mixing auxiliary agent comprises the following components by mass: 100 parts of solvent water, 20-40 parts of sulfur, 15-25 parts of zinc oxide, 5-15 parts of accelerator, 0.5-1.5 parts of antioxidant, and 3-5 parts of dispersant; wherein sulfur is a vulcanizing agent and zinc oxide is a vulcanization activator.
9. The nitrile latex gloves with high nano-calcium carbonate filling according to claim 7, characterized in that: The nitrile latex is high nitrile, wherein the mass percentage of acrylonitrile is 35% to 50%; the casein is commercially available edible casein; the cellulose is hydroxymethyl cellulose; and the defoaming agent is an organosilicon defoaming agent.
10. The method for preparing the nitrile latex gloves with high filling amount of nano calcium carbonate according to claim 7, characterized in that: The steps include: (1) adding casein, a mixing aid, nanocellulose and a defoaming agent to a nitrile latex according to the raw materials and their weight fractions as claimed in claim 7, stirring and dispersing the mixture uniformly to obtain a mixed emulsion; (2) adding the ultra-low calcium ion activity monodisperse nano-calcium carbonate slurry to the mixed solution obtained in step (1), stirring evenly to obtain a mixed material; (3) After cleaning the glove mold, preheat it to 60-70°C and immerse it in a coagulant for 5-10 seconds. After immersion, take out the glove mold, shake off the excess coagulant, and then put it into a 60-70°C oven for 4-6 minutes; (4) dipping the glove mold obtained in step (3) into the mixture obtained in step (2) for 5 to 10 seconds, then taking out the glove mold and dripping off the excess mixture, and then putting it into a 60 to 70° C. oven for 4 to 6 minutes; (5) immersing the glove mold obtained in step (4) in warm water at 40 to 50° C. for 10 to 20 seconds, then taking out the glove mold, shaking off excess water, and placing it in a 60 to 70° C. oven after curling for 4 to 6 minutes; (6) immersing the glove mold obtained in step (5) into the polyurethane solution for a dipping time of 5 to 10 seconds, then taking out the glove mold, shaking off the excess polyurethane solution, and then putting it into an oven at 120 to 130° C. for a drying time of 7 to 8 minutes, demoulding, and obtaining a nitrile latex glove with a high filling amount of nano-calcium carbonate; wherein the polyurethane solution is an aqueous emulsion with a concentration of 2 to 10 wt %, and the molecular weight of the polyurethane is in the range of 1000 to 10000.
Citation Information
Patent Citations
Method for improving mechanical properties of polypropylene carbonate (PPC) through calcium carbonate filled modification
CN103540113A
Preparation method of monodispersed nano-calcium carbonate with low surface energy
CN109850931A
High-stability low-salt nano calcium carbonate slurry and application thereof in preparation of powdered nitrile rubber
CN114957796A
Preparation method of nano calcium carbonate for photovoltaic sealant
CN116282115A